Covalently bonded nitrogen-doped carbon-nanotube-supported Ag hybrid sponges: Synthesis, structure manipulation, and its application for flexible conductors and strain-gauge sensors. (May 2015) - Zhao, Songfang; Gao, Yongju; Zhang, Guoping; Deng, Libo; Li, Jinhui; Sun, Rong; Wong, Ching-Ping
Abstract: Flexible strain-gauge sensors are an essential component in electronic devices, and pressure sensing is also an important function. Here, we report an ultrastable and highly sensitive sensor based on covalently bonded nitrogen-doped carbon-nanotube-supported Ag (N-CNT/Ag) hybrid sponges with hierarchical binary-network architectures via a unidirectional freezing technique. The covalent bonding utilizing hyperbranched polyglycerol (HPG) as bridges endows the sponges with structural stability under compression, oscillation, and bending modes. Moreover, a large number of Ag nanoparticles (NPs) decorated using HPG as templates could also enable the N-CNTs/Ag sponges to possess linear current–voltage behavior. Furthermore, the Ag NPs on the compartmental films can be considered as interlocked nanodomes, which not only enhance compression stress but also generate huge variation of resistance through variation of contact area under mechanical deformation. These novel designs featuring interlocked geometry and covalent bonding allow the hybrid sponges to act as strain-gauge sensors with high gauge factor (1.4) and excellent stability.